Law enforcement, social control and organized crime. Evidence from local government dismissals in Italy - Federico Cingano; Marco Tonello (Global Labor Organization (GLO), 2020)
Local governments suspected of Mafia infiltration can be dismissed in Italy through an administrative act not increasing formal deterrence but potentially signaling improved law enforcement among local communities. This paper finds that dismissals are associated to a persistent fall of petty crimes (e.g. thefts) but have no consequences on offenses more closely related to the activity of organized crime, as homicide, extortion, drug-trafficking or usury. Petty crimes are estimated to fall by around 10%, on average, a result that seems driven by the perception of enhanced deterrence (through media pressure, the signaling role of the policy, and other forms of social control) rather than induced by organized crime itself.
Keywords: K14; K42; D73; 330; crime; law enforcement; organized crime; social control